Impact of sex on response to neoadjuvant chemotherapy in patients with bladder cancer - D'Andrea, David; Black, Peter C; Zargar, Homayoun; Zargar-Shoshtari, Kamran; Zehetmayer, Sonja; Fairey, Adrian S; Mertens, Laura S; Dinney, Colin P; Mir, Maria C; Krabbe, Laura-Maria; Cookson, Michael S; Jacobsen, Niels-Erik; et al. (Urologic oncology, 2020)
OBJECTIVE: To assess the effect of patient's sex on response to neoadjuvant chemotherapy (NAC) in patients with clinically nonmetastatic muscle-invasive bladder cancer (MIBC). METHODS: Complete pathologic response, defined as ypT0N0 at radical cystectomy, and downstaging were evaluated using sex-adjusted univariable and multivariable logistic regression modeling. We used interaction terms to account for age of menopause and smoking status. The association of sex with overall survival and cancer-specific survival was evaluated using Cox regression analyses. RESULTS: A total of 1,031 patients were included in the analysis, 227 (22%) of whom were female. Female patients had a higher rate of extravesical disease extension (P = 0.01). After the administration of NAC, ypT stage was equally distributed between sexes (P = 0.39). On multivariable logistic regression analyses, there was no difference between the sexes or age of menopause with regards to ypT0N0 rates or downstaging (all P > 0.5). On Cox regression analyses, sex was associated with neither overall survival (hazard ratio 1.04, 95% confidence interval 0.75-1.45, P = 0.81) nor cancer-specific survival (hazard ratio 1.06, 95% confidence interval 0.71-1.58, P = 0.77). CONCLUSION: Our study generates the hypothesis that NAC equalizes the preoperative disparity in pathologic stage between males and females suggesting a possible differential response between sexes. This might be the explanation underlying the comparable survival outcomes between sexes despite females presenting with more advanced tumor stage.
Keywords: výsledek terapie; Male; retrospektivní studie; Chemotherapy, Adjuvant; sexuální faktory; nádory močového měchýře; Aged; mužské pohlaví; senioři; Treatment Outcome; lidé; ženské pohlaví; Humans; Sex Factors; adjuvantní chemoterapie; Retrospective Studies; Urinary Bladder Neoplasms; Female; lidé středního věku; Middle Aged